Marketing Intelligence for Strategic Growth - Malhan, Maulik (Journal of Advanced Research in Strategic Marketing Intelligence and Customer Engagement Optimization, 2025)
Marketing intelligence (MI) has become a fundamental driver of strategic growth in the modern business landscape. It refers to the systematic collection, analysis, and application of market, customer, and competitor data to guide business decision-making and achieve competitive advantage. This review article explores how marketing intelligence contributes to business growth by improving market understanding, optimizing customer engagement, and enhancing decision-making. The article also highlights key tools and technologies that facilitate marketing intelligence efforts, such as CRM systems, data analytics platforms, social media monitoring, and marketing automation tools. Additionally, best practices for leveraging MI to drive strategic growth are discussed, emphasizing the importance of clear objectives, cross-departmental collaboration, continuous monitoring, and investment in skilled talent. Ultimately, this paper demonstrates how businesses can use marketing intelligence to adapt to market changes, identify opportunities, and implement data-driven strategies that promote long-term growth and success.